Magnetotransport and thermopower of single Bi0.92Sb0.08 nanowires. Issue 10 (3rd July 2013) - Heiderich, Sonja; Toellner, William; Boehnert, Tim; Gluschke, Jan Goeran; Zastrow, Sebastian; Schumacher, Christian; Pippel, Eckhard; Nielsch, Kornelius
Abstract <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> This Letter reports on temperature‐dependent electrical measurements of single Bi0.92Sb0.08 nanowires with diameters between 220 nm and 350 nm. The magnetoresistance effect under transverse magnetic fields of ±2 T and the Seebeck coefficient S are measured in the temperature range of 50–300 K. Additionally, the influence of an annealing step on the transport properties is investigated. The as‐prepared wires show heterogeneous temperature dependent behavior, whereas the annealed wires show semiconductive behavior. The room temperature value of the resistivity of the wires is between 2 × 10–6 Ωm and 1.4 × 10–5 Ωm. Magnetoresistance effects up to 15% at 50 K for the as‐prepared nanowires and up to 23% for the annealed wires are observed. The temperature dependent Seebeck coefficient of single wires is determined. The as‐prepared wires show a rise of the absolute value of S with temperature and it seems to saturate at room temperature. In contrast to this, the annealed wires show a linear increase of S. The room temperature values of S are –55 µV K–1 and –45 µV K–1, respectively. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)